Modern Technologies and Gamification in Historical Education - Moseikina, Marina; Toktamysov, Saken; Danshina, Svetlana (Simulation & gaming, 2022)
Background The study aims to consider the prospect possibilities of gamification in historical education and its influence on the development of key professional competencies of workers necessary in current condition of humanitarian sphere development. Methods An experimental study theoretically substantiates the prospects for the gamification of education on the example of history education, in which 40 students from the Рeoples’ Friendship University of Russia and Sechenov First Moscow State Medical University took part. A pedagogical model of gamified history study has been developed and implemented into a 3-month online learning course “Technology for constructing historical interpretations.” The following technological tools were used to support the implementation of gamified learning: the Academy Learning Management System (LMS), the Facebook social network, social media information resources, augmented and virtual reality technologies. A survey was conducted on the Academy LMS platform, in which students were asked to assess the promising opportunities for the impact of gamified learning on the development of key professional competencies in terms of the degree of influence. Results The research results confirmed that the creation of a joint creative and expanded gaming experience leads to the acquisition of practical knowledge and allows learners to acquire skills that are highly relevant for professionals of the 21st century. The students confirmed that educational progress was achieved due to the effective organization of their learning activities, group changeover at the stages of developing historical interpretations, and gamification, which caused a feeling of excitement and qualitatively influenced the desire to achieve the best educational results. Gamified learning allowed educators to keep students' interest in the subject of study. Conclusions According to the results of a survey of students at the end of the course, it was concluded that gamification in history education has a positive effect on the evolutionary development of a personality adaptive to the socio-economic conditions of the 21st century. A model of the evolutionary vertical and horizontal development of the personality has been described.